Assessing Cell Competition in Human Pluripotent Stem Cell (hPSC) Cultures. Issue 5 (27th May 2022) - Price, Christopher J.; Barbaric, Ivana
Abstract: Cell‐cell interactions are required for development and homeostasis in multicellular organisms from insects to mammals. A critical process governed by these interactions is cell competition, which functions throughout development to control tissue composition by eliminating cells that possess a lower fitness status than their neighbors. Human pluripotent stem cells (hPSCs) are a key biological tool in modeling human development and offer further potential as a source of clinically relevant cell populations for regenerative medicine applications. Recently, cell competition has been demonstrated in hPSC cultures and during induced pluripotent stem cell reprogramming. In turn, these findings suggest that hPSCs can be used as a tool to study and model cell‐cell interactions during different stages of development and disease. Here, we provide a panel of protocols optimized for hPSCs to investigate the potential role that cell competition may have in determining the fate and composition of cell populations during culture. The protocols entail assessment of the competitive phenotype and the mode through which cell competition may lead to elimination of less‐fit cells from mosaic cultures with fitter counterparts. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Electroporation of hPSCs to establish a fluorescent reference cell line Support Protocol 1 : Single‐cell dissociation of hPSCs Support Protocol 2 : Single‐cell cloning of fluorescently labeled hPSCs Basic Protocol 2 : Separate culture and co‐culture proliferation assays Basic Protocol 3 : Assessing levels of apoptosis in hPSC cultures using flow cytometry Basic Protocol 4 : Transwell assay Support Protocol 3 : Immunohistochemistry and image quantification of cleaved caspase‐3 Basic Protocol 5 : Cell confrontation assay Basic Protocol 6 : Cell compression assay Basic Protocol 7 : Time‐lapse imaging to assess mechanical extrusion